Structural Complexity and Thermoelectric Properties of Quaternary and Quinary Tellurides (GexSn1–x)0.8(InySb1–y)0.13Te with 0 ≤ x, y ≤ 1. Issue 23 (16th October 2017) - Neudert, Lukas; Schwarzmüller, Stefan; Scheel, Manuel; Welzmiller, Simon; Oeckler, Oliver
Abstract : Starting from stoichiometric mixtures of the elements, quaternary and quinary solid solutions (Ge x Sn1– x )0.8 (In y Sb1– y )0.13 Te were obtained. Concerning the ratio Ge/Sn and Sb/In, respectively, lattice parameters of the metastable phases with rocksalt‐type average structures approximately obey Vegard's law. Stable phases correspond to a disordered rocksalt type at high temperature and to trigonal layered structures with van der Waal gaps at lower temperature as shown by temperature‐dependent powder X‐ray diffraction combined with TEM, which reveals layer‐like vacancy ordering, whose extent depends on composition and thermal treatment. In the long‐periodically ordered model compounds 21 R ‐Ge0.5 Sn0.5 InSbTe4 and 9 P ‐GeSnInSbTe5 studied by resonant scattering data at K ‐absorption edges, Sb and Sn concentrate near the van der Waals gaps. Compared to Ge0.8 Sb0.13 Te and Sn0.8 Sb0.13 Te, the simultaneous presence of In and Sn combines increased electrical conductivity with low thermal conductivity and enhanced thermoelectric properties in certain temperature ranges. Phase transitions correlate with changes of the thermoelectric properties. Abstract :